2018
DOI: 10.4236/jsemat.2018.84010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Li Ions on Al Electrodeposition from Dimethylsulfone

Abstract: The influence of LiCl coexistence with Al electrodeposition was investigated in a dimethyl sulfone, DMSO 2 , bath containing AlCl 3 at 403 K. The electrochemical behaviors of Li and Al ions were examined using Pt electrodes in the bath and the deposition mechanism was analyzed by cyclic voltammetry, CV, with an Al reference electrode in the bath. The coexistence of LiCl in the AlCl 3-DMSO 2 bath inhibited the cathodic current corresponding to Al deposition in the CV experiment. The amount of ca. 500 μmol Al de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…27 Furthermore, Kim reported that the intensity of the Al(DMSO 2 ) 3 3+ signals decreased upon adding LiCl to the electrolyte. 39 These results indicate that the addition of NR 4 Cl decreases the concentration of the Al 3+ species in the electrolyte involved in the Al electrodeposition, such as the solvated form of Al(DMSO 2 ) 3 3+ . Based on the results of 27 Al NMR spectroscopy, we discuss the change in the dissociation equilibrium of the ionic species in the electrolyte upon adding NR 4 Cl.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…27 Furthermore, Kim reported that the intensity of the Al(DMSO 2 ) 3 3+ signals decreased upon adding LiCl to the electrolyte. 39 These results indicate that the addition of NR 4 Cl decreases the concentration of the Al 3+ species in the electrolyte involved in the Al electrodeposition, such as the solvated form of Al(DMSO 2 ) 3 3+ . Based on the results of 27 Al NMR spectroscopy, we discuss the change in the dissociation equilibrium of the ionic species in the electrolyte upon adding NR 4 Cl.…”
mentioning
confidence: 78%
“…In contrast, sulfonebased solvents [25][26][27][28] have low volatility and inflammability. For example, dimethyl sulfone ((CH 3 ) 2 SO 2 , DMSO 2 ) [29][30][31][32][33][34][35][36][37][38][39][40][41] is inexpensive, compared to ionic liquids, and it can facilitate film formation with a current density of 50 mA cm −2 or more. However, since the melting point of DMSO 2 is 109 °C, the processing temperature is higher than those of other organic solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation